1998
DOI: 10.3171/jns.1998.89.3.0389
|View full text |Cite
|
Sign up to set email alerts
|

Defining thresholds for critical ischemia by using near-infrared spectroscopy in the adult brain

Abstract: Carotid endarterectomy provides a stable environment for exploring NIRS-quantified thresholds for SCI in the adult head.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
0
4

Year Published

2002
2002
2014
2014

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(54 citation statements)
references
References 24 publications
3
47
0
4
Order By: Relevance
“…Accordingly, changes from the preclamp period rather than absolute values seem to be more important to predict the occurrence of cerebral ischemia. This is in agreement with findings reported by Kirkpatrick et al [22] who demonstrated that the percentage change in rSo 2 , rather than its absolute value, is strictly correlated to the percentage decrease in cerebral blood flow.…”
Section: Discussionsupporting
confidence: 93%
“…Accordingly, changes from the preclamp period rather than absolute values seem to be more important to predict the occurrence of cerebral ischemia. This is in agreement with findings reported by Kirkpatrick et al [22] who demonstrated that the percentage change in rSo 2 , rather than its absolute value, is strictly correlated to the percentage decrease in cerebral blood flow.…”
Section: Discussionsupporting
confidence: 93%
“…A number of modalities have been introduced for detecting cerebral malperfusion during cardiovascular surgery or carotid artery surgery, including transcranial Doppler ultrasound [1][2][3] and near-infrared spectroscopy (NIRS) [1][2][3][4][5][6][7][8][9]. We have routinely used NIRS monitoring since 1998 and have recognized that the regional oxygen saturation (rSO2) promptly drops upon temporary circulatory arrest, and then recovers as systemic circulation resumes in patients undergoing aortic surgery with selective cerebral perfusion (SCP).…”
Section: Introductionmentioning
confidence: 99%
“…NIRS has been used to monitor patients with head injuries [2, 3], during cerebral thrombolysis [4, 5], cardiopulmonal bypass [6, 7], and carotid endarterectomy [8, 9, 10]. However, validity and clinical significance are judged controversially [11, 12, 13, 14, 15].…”
Section: Introductionmentioning
confidence: 99%